2009
DOI: 10.4000/rei.4058
|View full text |Cite
|
Sign up to set email alerts
|

Appels d’offres concurrentiels et avantage au sortant, une étude empirique du secteur du transport public urbain en France

Anne Yvrande-Billon

Abstract: Cet article porte sur les déterminants de la reconduction des contrats de services publics attribués par appels d’offres concurrentiels. Partant de la constatation que ces contrats changent très rarement de mains, on s’interroge sur les raisons de cette stabilité des prestataires de services publics. Plus précisément, l’analyse empirique porte sur le secteur du transport public urbain en France et cherche à identifier les variables explicatives de l’avantage au sortant. La base de données que nous avons constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Coviello and Mariniello (2014) found that increased publicity has a positive effect on the number of bidders, which can make alternation more likely. Yvrande-Billon (2009) found that when the contract is awarded by means of a competitive tender-which could be seen as an indicator of transparency-the probability of renewal with the incumbent is lower than when the contract is hand-picked. Coviello, Guglielmo, and Spagnolo (2018) found that more discretion in the procurement process is positively related to the probability of incumbents winning the new contract, and that incumbent renewal can actually improve performance.…”
Section: Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Coviello and Mariniello (2014) found that increased publicity has a positive effect on the number of bidders, which can make alternation more likely. Yvrande-Billon (2009) found that when the contract is awarded by means of a competitive tender-which could be seen as an indicator of transparency-the probability of renewal with the incumbent is lower than when the contract is hand-picked. Coviello, Guglielmo, and Spagnolo (2018) found that more discretion in the procurement process is positively related to the probability of incumbents winning the new contract, and that incumbent renewal can actually improve performance.…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…Competitive tenders in public services are seen as a means of introducing competition into sectors with natural monopoly conditions (Demsetz 1968); however, incumbents very often retain contracts. Although the debate is ongoing, some authors have construed the lack of alternation as a symptom of insufficiently effective competition and collusive behavior (Yvrande-Billon 2009). Lalive, Schmutzler, and Zulehner (2015) performed a comparative analysis of negotiations with the incumbent and open auctions in the procurement of railway services in Germany, finding that negotiations correlate with lower consumer surplus and higher prices.…”
mentioning
confidence: 99%